Investigating the educational effectiveness of gamebased learning for IT education - Ariffin, M.M. (Institute of Electrical and Electronics Engineers Inc., 2016)
This study aimed to investigate the effectiveness of game-based learning in supporting IT education particularly in network security topics. To attain this objective, the post-test was administered to the participant. This study adopted the Quasi-experimental research design involving 91 participants. The finding from this study suggested that participants who participated in game-based learning outperformed the participants in the control group. Â© 2016 IEEE.